Has the tide turned? Marine tourism and female empowerment: The case of Galicia - Crespi-Vallbona, Montserrat; Cooper, Laureen (Hotel and Tourism Management, 2023)
Several fishing families on the Spanish coast use marine tourism as a means to complement their finances. The aim of this research is the analysis of this phenomenon characterised by a prominent mood of female empowerment, as a large number of the entrepreneurs and workers in this area are women, and also by its sustainable management, since it is an activity that respects and cares for the environment, while also safeguarding local identities and cultural traditions. The case study is the Galician coast, a pioneer region for this type of tourism. The methodology of analysis is qualitative, involving in-depth interviews with women representing the fishing communities of Redondela, Cambados and Cesantes, as well as the Galician Government’s tourism plans. The research contributes to the theory by studying and conceptualising marine tourism as another way to reinforce local identity and sense of belonging. As for its practical implications, it highlights the predominant role of women (who are traditionally invisible in this sector) and the sustainable, bottom-up governance of this form of tourism.